The Legitimacy of Wiretapping Results from the Komisi Pemberantasan Korupsi as Evidence in Corruption Cases Linked to Indonesian Legal Provisions - Hasanah, Hetty (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The increasingly widespread criminal acts of corruption have made corruption an extraordinary crime. Currently, there is already an independent institution created based on law, namely the Komisi Pemberantasan Korupsi (hereinafter referred to as the KPK). In itsdevelopment, the KPK has been able to uncover several corruption cases in Indonesia, with various pieces of evidence including evidence in the form of intercepted communications from the perpetrators who have misused this communication facility to commit crimes. This research was conducted to find out the authority of KPK to wiretap the cases it handled and the validity of the wiretapping results carried out by the KPK as evidence. The previous research was about wiretapping as legal evidence in criminal cases so that it can support research on the validity of KPK wiretapping results as evidence in corruption cases. Based on the results of previous research, it is known that everyone is prohibited from wiretapping any information, but wiretapping can be done for the benefit of the criminal justice process. Meanwhile, this research was conducted to obtain clear information about the validity of wiretapping results as evidence in corruption cases.